2015
DOI: 10.2106/jbjs.n.00169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Cost-Effectiveness of Unicompartmental Knee Arthroplasty Compared with Total Knee Arthroplasty in the U.S.

Abstract: Unicompartmental knee arthroplasty is an economically attractive alternative in patients sixty-five years of age or older, and modest improvements in implant survivorship could make it a cost-effective alternative in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…Multiple studies have demonstrated that conclusions related to the cost-effectiveness of UKA, TKA and HTO are highly sensitive to annual revision rates [8,7880]. For example, it has been demonstrated that UKA is cost-effective compared to TKA if the annual revision rate is <4.0 per year in 78 year old patients [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated that conclusions related to the cost-effectiveness of UKA, TKA and HTO are highly sensitive to annual revision rates [8,7880]. For example, it has been demonstrated that UKA is cost-effective compared to TKA if the annual revision rate is <4.0 per year in 78 year old patients [78].…”
Section: Discussionmentioning
confidence: 99%
“…Many distinct advantages of UKA compared to total knee arthroplasty (TKA) have been reported including lower perioperative morbidity [2,3], lower risk for infection [4], less blood loss [5], accelerated recovery [6,7] and improved range of motion [2,7]. A recent cost-effectiveness study demonstrated that medial UKA is preferable to TKA with decreased lifetime costs and improved quality of life in patients over 65 years of age [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Cost-effective analysis calculated in orthopaedic literature has demonstrated the value provided to economies as a whole with timely, and age-specific therapy in joint replacement surgery. 3 Time to surgery also plays a role in providing value to this patient population. A study comparing cost-utility analysis for carpal tunnel release in the United States and Canada showed significant health-related quality of life improvements calculated to be $7,758/quality-adjusted life year greater in the U.S. population compared with Canada's due to shorter wait times.…”
Section: Restoration Of Form and Functionmentioning
confidence: 99%
“…In view of excellent functional results, good long-term survivorship, and advantages in terms of cost efficiency, unicompartmental knee arthroplasty (UKA) can make a significant contribution to meet the rapidly growing demand for knee arthroplasty [1][2][3][4][5]. Since the aseptic loosening of the tibial component, misinterpretation of radiolucent lines and cementation errors remain major reasons for revision in UKA [6][7][8][9]; improvements of the interface between prosthesis, cement, and trabecular bone, as well as the optimization of minimally invasive surgical techniques, are of outstanding importance [10,11].…”
Section: Introductionmentioning
confidence: 99%